2017
DOI: 10.1177/1093526616686233
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Intraocular Immature Teratoma Associated With Sacrococcygeal Teratoma

Abstract: Intraocular teratomas are rare neoplasms with only three previously reported cases. We present the fourth case of intraocular teratoma and the second associated with sacrococcygeal teratoma. While the nature of the association between intraocular teratomas and sacrococcygeal teratomas is unclear, it suggests a need for careful ophthalmologic follow-up of infants with congenital sacrococcygeal teratomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…The clinical characteristics of primary sacral benign tumors were distinct from the one of spinal benign tumors. Some rare histologic types should be considered when the differential diagnosis [17][18][19][20][21][22][23]. It has been reported that hemangioma was the most frequent benign primary spine tumor in one hospital of China, which was different from the region of the sacrum and our database showed giant cell tumor was the most common histological type at the sacrum [1].…”
Section: Discussionmentioning
confidence: 68%
“…The clinical characteristics of primary sacral benign tumors were distinct from the one of spinal benign tumors. Some rare histologic types should be considered when the differential diagnosis [17][18][19][20][21][22][23]. It has been reported that hemangioma was the most frequent benign primary spine tumor in one hospital of China, which was different from the region of the sacrum and our database showed giant cell tumor was the most common histological type at the sacrum [1].…”
Section: Discussionmentioning
confidence: 68%
“…The clinical characteristics of primary sacral benign tumors were distinct from the one of spinal benign tumors. Some rare histologic types should be considered when the differential diagnosis [19][20][21][22][23][24][25]. It has been reported that hemangioma was the most frequent benign primary spine tumor in one hospital of China, which was different from the region of sacrum and our database showed giant cell tumor was the most common histological type at the sacrum [1].…”
Section: Location Distribution Of Sacral Tumors and Tumor-like Lesionsmentioning
confidence: 68%
“…Sacrococcygeal teratoma is the most common extragonadal germ cell tumor in neonates and infants [19][20][21]. However, this lesion sometimes occurs in the adults.…”
Section: Discussionmentioning
confidence: 99%